A desoxyanisoin- and furfurylamine-derived high-performance benzoxazine thermoset with high glass transition temperature and excellent anti-flammability. (July 2021) - Wang, Xin; Niu, Haoxin; Huang, Jiali; Song, Lei; Hu, Yuan
Highlights: Poly(BHDB-Bz) exhibited a relatively high glass transition temperature (285 o C) Poly(BHDB-Bz) displayed a high LOI value (40.0%) and a UL-94 V-0 rating owing to its superior charring ability Poly(BHDB-Bz) showed an extremely low HRC (35.5 J/(gK)) which is lower than most synthetic polymers Despite many superior advantages including high heat resistance, low dielectric constant, low water absorption, and low curing shrinkage, the flammability of polybenzoxazines restricts their widespread applications in electronic realms. It is thereby essential to synthesize flame retardant polybenzoxazines for broadening their applications. In this work, we synthesized an anti-flammable bio-based benzoxazine monomer (BHDB-Bz) derived from furfurylamine. As a control sample, another bio-based benzoxazine monomer (BPA-Bz) was also synthesized from furfurylamine and bisphenol A. The molecular structure of BHDB-Bz and BPA-Bz was confirmed by FTIR, and 1 H- and 13 C-NMR spectra. Two kinds of bio-based polybenzoxazines, poly(BHDB-Bz) and poly(BPA-Bz), were obtained through thermally-induced ring-opening polymerization. Poly(BHDB-Bz) exhibited a relatively high glass transition temperature (285 °C), a high initial decomposition temperature (379 °C under nitrogen and 388 °C under air), and an extremely high char yield under nitrogen (65.9%), all of which were better than poly(BPA-Bz). Benefitting from the superior charring ability of desoxyanisoin structure, poly(BHDB-Bz) exhibited outstanding anti-flammability, whereas poly(BPA-Bz) was flammable. Specifically, poly(BHDB-Bz) displayed a high LOI value (40.0%), a UL-94 V-0 rating, and an extremely low heat release capacity (35.5 J/(gK)). This work provides a facile and sustainable strategy for developing an anti-flammable benzoxazine thermoset without introducing flame retardant additives.